PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN KECERDASAN INTELEKTUAL TERHADAP PEMAHAMAN AKUNTANSI PADA MAHASISWA PRODI AKUNTANSI DI KOTA BATAM - Paulina, Paulina; Janrosl, Viola Syukrina E (LPPM Universitas Putera Batam, 2023)
The aim of this research was to determine the effect of emotional intelligence, spiritualintelligence and intellectual intelligence on accounting comprehension. The methodused in the findings contained in this study is a quantitative-based research byconducting multiple linear analysis. The population in this study were accountingstudy program students at Universal University, Batam University, BatamInternational University, Batam State Polytechnic and Riau Islands University. Themethod used for sampling is simple random sampling. The results of research basedon a study will certainly be able to prove that emotional intelligence, spiritualintelligence and intellectual intelligence have a significant effect on understanding ofaccounting in accounting study program students in Batam City